KIF11 promotes vascular smooth muscle cell proliferation by regulating cell cycle progression and accelerates neointimal formation after arterial injury in mice - Wang, Gengqiao; Zhao, Peng; Yin, Chuanzheng; Zheng, Xichuan; Xie, Yuhang; Li, Xuan; Shang, Dan; Shao, Shuyu; Chen, Hao; Wei, Li; Song, Zifang (Frontiers in Pharmacology, 2024)
Background and aims: One of the primary causes of lumen narrowing is vascular injury induced during medical procedures. Vascular injury disrupts the integrity of the endothelium, triggering platelet deposition, leukocyte recruitment, and the release of inflammatory factors. This, in turn, induces the proliferation of vascular smooth muscle cells (VSMCs), leading to neointima formation. However, the molecular mechanism underlying VSMC proliferation following injury remains unknown. KIF11 is critical in regulating the cell cycle by forming bipolar spindles during mitotic metaphase. This process may contribute to VSMCs proliferation and neointima formation following vascular injury. Yet, the function of KIF11 in VSMCs has not been elucidated. This study aims to investigate the role and mechanisms of KIF11 in regulating VSMCs cycle progression and proliferation. Methods: After conducting biological analysis of the transcriptome sequencing data from the mouse carotid artery injury model and the cell transcriptome data of PDGF-BB-induced VSMCs , we identified a potential target gene, KIF11, which may play a crucial role in vascular injury. Then we established a vascular injury model to investigate how changes in KIF11 expression and activity influence in vivo VSMCs proliferation and neointimal formation. In addition, we employed siRNA and specific inhibitors to suppress KIF11 expression and activity in VSMCs cultured in vitro to study the mechanisms underlying VSMCs cycle progression and proliferation. Results: The results of immunohistochemistry and immunofluorescence indicate a significant upregulation of KIF11 expression in the injured vascular. The intraperitoneal injection of the KIF11 specific inhibitor, K858, partially inhibits intimal hyperplasia in the vascular injury model. In vitro experiments further demonstrate that PDGF-BB upregulates KIF11 expression through the PI3K/AKT pathway, and enhances KIF11 activity. Inhibition of both KIF11 expression and activity partially reverses the pro-cycle progression and pro-proliferation effects of PDGF-BB on VSMCs. Additionally, KIF11 overexpression partially counteracts the proliferation arrest and cell cycle arrest induced by inhibiting the PI3K/AKT pathway in VSMCs. Conclusion: Our study highlights the crucial role of KIF11 in regulating the cycle progression and proliferation of VSMCs after vascular injury. A comprehensive understanding of these mechanisms could pave the way for potential therapeutic interventions in treating vascular stenosis.